Optimization of surface roughness on duplex stainless steel in dry milling - Nurul Hidayah, Razak; Mohammad Rizal, Md Ali (Springer Singapore, 2024)
In manufacturing industry, surface roughness is one of the crucial factors affecting the production costs and machining duplex stainless steel becomes difficult due to its mechanical properties. This study was performed on a duplex stainless steel in dry milling operation using carbide tools. Response surface methodology (RSM) is utilised to identify main cutting parameter that affects the quality of surface roughness as well as optimizing the operation. It is found that feed rate, f contributes to the highest factor affecting the quality of surface roughness, Ra followed by the speed of the cutting, VC and depth-of-cut, DOC. An optimum machining parameters speed of cutting of 78.283 mm/min, rate of feed of 0.100 mm/tooth and axial depth of 0.834 mm is identified as the optimum values.